Computing Dispersion Coefficient of Model Waste Stabilization Ponds - Koh, Hoy Lye; Lim, Poh Eng (1991)
Previous methods of determining dispersion coefficient of waste stabiliz.ation ponds used age distribution function observed at the outlet of the pond. Typically, concentration measurements for periods of up to two or three times the theoretical retention time are needed. This poses considerable problems for ponds with a long retention time. This paper presents an efficient method of computing the dispersion coefficient that requires a much shorter period of observation. Typically less than 0.4 times the theoretical retention time is adequate. Results obtained are comparable or superior to those obtained 1Yy previous methods.